2006
DOI: 10.1074/jbc.m511064200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Oxidative Metabolism by Mitochondrial Frataxin Inhibits Cancer Growth

Abstract: More than 80 years ago Otto Warburg suggested that cancer might be caused by a decrease in mitochondrial energy metabolism paralleled by an increase in glycolytic flux. In later years, it was shown that cancer cells exhibit multiple alterations in mitochondrial content, structure, function, and activity. We have stably overexpressed the Friedreich ataxia-associated protein frataxin in several colon cancer cell lines. These cells have increased oxidative metabolism, as shown by concurrent increases in aconitase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
150
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(164 citation statements)
references
References 47 publications
11
150
1
2
Order By: Relevance
“…Studies in mice, whose liver cells were devoid of frataxin, a mitochondrial protein that upregulates OXPHOS-mediated ATP synthesis, have shown a strong correlation between mitochondrial impairment and tumor promotion (Thierbach et al, 2005). Later in vitro studies found that overexpression of frataxin in colon cancer cell lines enhanced mitochondrial respiration and concomitantly diminished their tumorigenicity (Schulz et al, 2006). Similarly, genetic manipulation of the levels of PGC1a, a transcription factor whose activity fosters mitochondrial biogenesis, OXPHOS and fatty acid oxidation, revealed that knockout of PGC1a provokes intestinal tumor susceptibility whereas its overexpression hampers colorectal carcinogenesis (D'Errico et al, 2011).…”
Section: The Metabolic Pattern Of Cancer Cellsmentioning
confidence: 99%
“…Studies in mice, whose liver cells were devoid of frataxin, a mitochondrial protein that upregulates OXPHOS-mediated ATP synthesis, have shown a strong correlation between mitochondrial impairment and tumor promotion (Thierbach et al, 2005). Later in vitro studies found that overexpression of frataxin in colon cancer cell lines enhanced mitochondrial respiration and concomitantly diminished their tumorigenicity (Schulz et al, 2006). Similarly, genetic manipulation of the levels of PGC1a, a transcription factor whose activity fosters mitochondrial biogenesis, OXPHOS and fatty acid oxidation, revealed that knockout of PGC1a provokes intestinal tumor susceptibility whereas its overexpression hampers colorectal carcinogenesis (D'Errico et al, 2011).…”
Section: The Metabolic Pattern Of Cancer Cellsmentioning
confidence: 99%
“…Neoplastic phenotype has often been associated to alterations in mitochondria physiology and morphology, to the point that a defect in oxidative phosphorylation was considered a hallmark of cancer [28,29]. Although there is no real indication that defective phosphorylation is an absolute feature of cancer cells, there is no doubt that many cancers display aerobic glycolysis.…”
Section: P2x 7 and Cancermentioning
confidence: 99%
“…Several groups reported that tumour aggressiveness correlates with a low-mitochondrial respiratory chain activity, and that enhancement of OXPHOS can reduce tumour growth (Hervouet et al, 2005;Schulz et al, 2006). Furthermore, a number of mitochondrial enzyme deficiencies are linked to inherited neoplasia (Gottlieb and Tomlinson, 2005).…”
Section: Mitochondrial Physiology In Cell Proliferation and Tumour Prmentioning
confidence: 99%